TEACHING-LOVING-CARING (ASAH-ASIH-ASUH) AND SEMI-MILITARY EDUCATION ON CHARACTER EDUCATION MANAGEMENT - Asep Sukendar; Husaini Usman; Cepi Safrudidin Abdul Jabar (LPMPP Universitas Negeri Yogyakarta, 2019)
Character education for students is important for their future because personal character traits determine the quality of human life. This qualitative study aims to analyze the planning and implementation of character education at Taruna Nusantara Senior High School (SHS), Magelang - a boarding senior high school that combines teaching-loving-caring (asah-asih-asuh) and semi-military education. The unit of analysis consists of individuals and group of subjects directly or indirectly involved in the education process at the researched school and the surrounding, as well as the artifacts. The data are collected through interview, observation, and documentation, and are subsequently analyzed using Huberman and Saldana’s interactive model. The results indicate that, in the planning, the school put more emphasis on three characteristics in character education that characterizes the school: religiosity, morality and leadership. The planning of character education is participatory and integrated. It is implemented in and around the boarding school learning environment. The activities include teaching, training, parenting, and student development.